2009
DOI: 10.4049/jimmunol.0803113
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 Ligand Induces NF-κB Activation and Various Fates of Multiple Myeloma Cells Depending on IFN-α Production

Abstract: Multiple myeloma (MM) cells express TLR. It has been shown that TLR ligands induce the proliferation, survival, and immune surveillance escape of MM cells through MyD88-TLR pathways. Deciphering TLR function in MM cells will help in understanding the mechanisms of tumor cell growth. In this study, we examined the response of MM cells to the MyD88-independent/TIR-domain-containing adapter-inducing IFN-β-dependent TLR3. Deregulation of NF-κB pathway is a feature of MM cells, and we wondered whether TLR3 activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 48 publications
3
39
0
Order By: Relevance
“…Through triggering NF-κB activation, TLR3 signal transduction may facilitate multiple myeloma cell survival. 45 It is also reported that TLR3 can promote inflammatory via mTOR to activate NF-κB in human oral keratinocytes. 46 In innate immunity, TLR3 triggers the activation of NF-κB and IRF3, generates type I interferons (IFNs) and promotes dendritic cell maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Through triggering NF-κB activation, TLR3 signal transduction may facilitate multiple myeloma cell survival. 45 It is also reported that TLR3 can promote inflammatory via mTOR to activate NF-κB in human oral keratinocytes. 46 In innate immunity, TLR3 triggers the activation of NF-κB and IRF3, generates type I interferons (IFNs) and promotes dendritic cell maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our findings demonstrated that LPS-induced cell proliferation was dependent on JNK, ERK and p38 signaling, suggesting that these pathways were involved in TLR4 ligand-induced myeloma cell proliferation. Interestingly, Chiron 9 et al reported that TLR3 ligand also induced NFκB and MAPK pathway activation in MM cells. These findings suggest that different TLR ligands may induce the same or similar signaling pathway activation in MM cells and exert their effects on myeloma cell growth, survival and development of drug resistance.…”
Section: Hmcl Primary Myeloma Cells DC and Culture Mediummentioning
confidence: 99%
“…TLR signaling induces Erk1/2 MAP kinase and NF-B activation in MM and colon cells that could contribute to malignant transformation (15). NF-B activation, either through mutations or interactions with the microenvironment, has been involved in the progression of many cancers, including MM (16).…”
mentioning
confidence: 99%